Edge of polar cap patches. Issue 4 (6th April 2016) - Hosokawa, K.; Taguchi, S.; Ogawa, Y.
Abstract: On the night of 4 December 2013, a sequence of polar cap patches was captured by an all‐sky airglow imager (ASI) in Longyearbyen, Norway (78.1°N, 15.5°E). The 630.0 nm airglow images from the ASI of 4 second exposure time, oversampled the emission of natural lifetime (with quenching) of at least ∼30 sec, introduce no observational blurring effects. By using such high‐quality ASI images, we succeeded in visualizing an asymmetry in the gradients between the leading/trailing edges of the patches in a 2‐D fashion. The gradient in the leading edge was found to be 2–3 times steeper than that in the trailing edge. We also identified fingerlike structures, appearing only along the trailing edge of the patches, whose horizontal scale size ranged from 55 to 210 km. These fingers are considered to be manifestations of plasma structuring through the gradient‐drift instability (GDI), which is known to occur only along the trailing edge of patches. That is, the current 2‐D observations visualized, for the first time, how GDI stirs the patch plasma and such a mixing process makes the trailing edge more gradual. This result strongly implies a close connection between the GDI‐driven plasma stirring and the asymmetry in the large‐scale shape of patches and then suggests that the fingerlike structures can be used as markers to estimate the fine‐scale structure in the plasma flow within patches. Key Points: Fingerlike signatures of plasma instability are identified within polar cap patches Gradient in the leading edge of patches is sharper than that in the trailing edge Plasma mixing through the plasma instability determines the shape of patches